Legal Consequences Of Authentic Deeds Made Based On Oral Document Verification Without Written Evidence - Khadijah Khadijah; Edi Tarsono; Rr. Utji Sri Wulan Wiryandari (International Journal Of Humanities Education and Social Sciences (IJHESS), 2026)
Against agreements including name loan agreements are generally set forth in an authentic Acte in order to have strong evidentiary power. An authentic Acte is a document made in accordance with the provisions of the form regulated by laws and regulations and drawn up by or in the presence of a Civil Servant authorized at the location of the Acte. The position of Notary is regulated in precisely in Clause 1 Number 1 UUJN. The provision states that a notary is a Civil Servant who has authority in making authentic Actes as well as other authorities as stipulated in this law. In his capacity as a Civil Servant, the notary provides explanations or testimonies regarding everything seen, witnessed and experienced by him that is done by other parties. This research is descriptive-analytical in nature, comprehensively, systematically, and thoroughly describing the legal consequences of authentic deeds made based on verbal document verification without supporting written evidence, particularly in relation to the notary's liability to third parties who suffer losses. The type of research used is normative legal research, which is research based on legal norms contained in legislation, legal doctrines, and related jurisprudence. An authentic Acte made only on the basis of oral verification of documents without being supported by written evidence carries serious legal consequences, namely the loss of authenticity and legal force of the Acte. This causes the Acte to be declared null and void or at least legally defective, contrary to the provisions Clause 1868 Civil Code, which requires written documents as a basis for making authentic Actes. As a result, the notary who made the Acte must be legally responsible for losses suffered by third parties, including criminal, administrative, civil, and ethical liability, which confirms that the notary's liability is multidimensional in order to maintain the integrity of his profession.